SISTEM INFORMASI PINJAMAN BUKU PERPUSTAKAAN BERBASIS ANDROID MENGGUNAKAN FLUTTER PADA SD NEGERI CBM DEWI SARTIKA KOTA SUKABUMI - wanda lestari (Jurnal Teknologi Informatika dan Rekayasa Terapan, 2026)
The development of information technology has significantly transformed library management systems from manual to digital systems that are more efficient. The problem at SDN CBM Dewi Sartika Sukabumi is that the book borrowing process is still conducted manually, leading to issues such as data loss, recording errors, and difficulty in tracking book availability. This study aims to design and develop an Android-based book borrowing information system using Flutter to improve library service effectiveness. The research method used is Research and Development (R&D) with a waterfall model approach. Data were collected through observation, interviews, and literature study. The system was developed using Flutter as a framework and SQLite as a local database. The results show that the system can facilitate book data management, borrowing, returning, and automatic fine calculation. In conclusion, the implementation of this system improves efficiency and accuracy in school library services.